2015
DOI: 10.1016/j.ijsu.2015.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic versus open complete mesocolic excision for right colon cancer

Abstract: Laparoscopic CME is a safe, feasible, and effective minimally invasive procedure for right colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
4
35
0
Order By: Relevance
“…The postoperative complication rate showed no statistical difference between the laparoscopic CME and open CME groups. The number of lymph nodes harvested in the laparoscopic CME group was slightly higher than that in the open CME group, but there was no statistical difference, which is in line with other reports [14] . All of the patients received follow-ups in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The postoperative complication rate showed no statistical difference between the laparoscopic CME and open CME groups. The number of lymph nodes harvested in the laparoscopic CME group was slightly higher than that in the open CME group, but there was no statistical difference, which is in line with other reports [14] . All of the patients received follow-ups in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The two vascular injuries of the jejunal branch of SMV were repaired uneventfully. The mean number of harvested lymph node was 41.9 and this number is found be high considering the current literature data in open, classical laparoscopic and robotic CME series (1)(2)(3)(4)(5)7,16). The number of harvested lymph nodes is an important surrogate marker for the quality of surgical resection and prognosis of the disease (17).…”
Section: Discussionmentioning
confidence: 86%
“…In its original definition, CME was first described using an open approach, and in the following years, laparoscopic approach has also been preferred because of the advantages of minimal invasive surgery in the postoperative recovery period (4,5). However, some disadvantages of classical laparoscopic surgery, including restriction of movement due to the use of rigid instruments, instability of the camera and tissue traction can make this operation cumbersome, especially during vascular dissection and intracorporeal anastomosis of the procedure (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The lengths of resected specimens in the laparoscopic and open groups were the same (216±71 vs. 204±51 mm, respectively, p=0.322), as were the average number of harvested lymph nodes (14±6 vs. 13±5, respectively, p=0.313). 16 Kang et al, 2014 demonstrated that, the effect of the number of harvested lymph nodes after right colon cancer surgery on oncological outcomes has recently been emphasized. Harvesting an adequate number of lymph nodes is essential for accurate tumor staging in the surgical treatment of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%